11-1/2y=3+6y

Simple and best practice solution for 11-1/2y=3+6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-1/2y=3+6y equation:



11-1/2y=3+6y
We move all terms to the left:
11-1/2y-(3+6y)=0
Domain of the equation: 2y!=0
y!=0/2
y!=0
y∈R
We add all the numbers together, and all the variables
-1/2y-(6y+3)+11=0
We get rid of parentheses
-1/2y-6y-3+11=0
We multiply all the terms by the denominator
-6y*2y-3*2y+11*2y-1=0
Wy multiply elements
-12y^2-6y+22y-1=0
We add all the numbers together, and all the variables
-12y^2+16y-1=0
a = -12; b = 16; c = -1;
Δ = b2-4ac
Δ = 162-4·(-12)·(-1)
Δ = 208
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{208}=\sqrt{16*13}=\sqrt{16}*\sqrt{13}=4\sqrt{13}$
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(16)-4\sqrt{13}}{2*-12}=\frac{-16-4\sqrt{13}}{-24} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(16)+4\sqrt{13}}{2*-12}=\frac{-16+4\sqrt{13}}{-24} $

See similar equations:

| |3n-4|=-1 | | 2u^2-5u-18=0 | | -6x+1=14x5 | | 12=-3(2x+2)+7x | | |3n-4|=1 | | 90=12x+42 | | 3x/4-7/5=2x/10 | | 0.1x-0.6x-14=1 | | -3a+3+4a=10-21 | | x(4)=2x | | 6x-10=4x+22 | | 2+5.7t-4.9t^2=0 | | 2=​2/m−7 | | 1.5t^2-24t=0 | | x+5=-81 | | 4f-16+2f=3f+11 | | x+2(x-7)=3x-7 | | 4r=21+2.50r | | (4x+9)+(4x+8)+(4x)=(4x)+4x)+(5x+6) | | F(x)=5/6x-15 | | 3z+15=48 | | 8x-2(3x-5)=24 | | 8(5x-3=6(-3x-4) | | -1/8c=-5/4 | | 2r-3/5=3 | | 3(x-4)=2x=6 | | 6x-12=18-8x | | (4x+9)+(4x+8)+(4x)=(4x)=(4x)+(5x+6) | | 0.7x-0.4(50+x)=-0.1(50) | | 3x+4(x+6)=6x-4x+x | | 4x+8=-4(2x-7)+2x | | 1/3(8x-9)=x+9/6 |

Equations solver categories